Never too old to fight breast cancer: A case report. Issue 9 (March 2018) - Zuradelli, Monica; Masci, Giovanna; Ferraro, Emanuela; Losurdo, Agnese; De Sanctis, Rita; Torrisi, Rosalba; Santoro, Armando
Abstract: Rationale: Breast cancer is the most common cancer affecting females worldwide and its lifetime risk increases with age. Human epidermal growth factor receptor gene-2 (HER-2) positive breast cancer represents about 20% of all breast cancers, 1 out of 10 is diagnosed in women over 70 years of age. It tends to be more aggressive and to spread more quickly than other subtypes, but the introduction in clinical practice of new anti-HER-2 agents combined with chemotherapy has significantly improved progression free and overall survival. Elderly patients are frequently undertreated because of concerns about their age, performance status, and comorbidities. Here, we report a case of an octogenarian patient treated with T-DM1 with brilliant results. Patient concerns: An 87 years old woman affected with HER-2 positive breast cancer presented progression of disease with lymph node and skin metastases after 3 lines of chemoimmunotherapy. Diagnoses: Breast cancer in elderly patient, lymph node, and skin metastases. Interventions: Chemoimmunotherapy (trastuzumab emtansine). Outcome: Objective response of the disease and significant clinical benefit. Lessons: This case clearly suggests that age and comorbidities do not always represent an absolute contraindication to combined treatments.